(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
This thesis analyzes the choice of a specific style of teaching foreign languages to students studying at higher institutions of rural agriculture, the correct distribution of study time, the correct use of special dictionaries, the correct selection of special texts, independent thinking of students, oral statement of their thoughts and clear and correct expression in written forms is shown that they are the main sources of speech development.